Mudando a história, “reinventando” a nação : um estudo sobre os governos de Lula (2003-2011) no Brasil e Rafael Correa (2007-2017) no Equador - Gavilanes, Jorge Gerardo Alarcón (2021)
At the turn of the 21st century, Latin America is experiencing in some countries a movement from neoliberal governments to leftwing governments. Two of these countries, despite their differences, seem to have some similarities in this historical process, which we propose to study in this dissertation. These are Lula's Brazil (20032010) and Rafael Correa's Ecuador (20072017). We believe that, in these two countries, their governments, in addition to carrying out important political, cultural, economic and social reforms moving away from neoliberalism, also had similarities in a project to “reinvent” the nation, in a more inclusive way, trying to shift the trajectory traditional elitist domain and social exclusion in them. To carry out this study, it is necessary to have a documentary body that includes newspapers, such as El Universo and Telegrafo de Ecuador, Folha de S. Paulo and the State of S. Paulo de Brasil, laws and legal documentation of both countries. Such as, the Constitution, decrees, among others; audiovisual advertisements related to the idea of nation, posters and advertisements. If in the theoretical field some concepts are relevant in research, such as nation, neoliberalism, revolution and the left, the method of analysis implies comparative history. With it, it will be possible to carry out the contrast of events and obtain explanations that go beyond times and particular spaces, within the period that involves the two governments. Thus, we hope to contribute to the understanding of this historical process that involves Brazil and Ecuador in Latin America at the turn and the first decades of the new millennium.